(untitled) (Revista Científica Compendium, 2014)
The aim of this study was to assess the quality of a graduate course from the student viewpoint and which is under e-learning modality. For the assessment, a model of internal criterium was made by the authors based on their own experiences as experts in virtual education and in line with the literature review on the topic of quality of e-learning in university education. The applied model focuses on the following components: (a) evaluation criteria (must be), represented by: instructional design, role of teachers, technology and organization; (b) the dynamics of the instructional process (what to do), which includes actions, interactions and transactions between the actors of the process during the development of projects, tasks and activities planned for the course; and (c) the prole of the student competence (being), according to the general course learning objective. An accessible sample to researchers was made of n= 17 subjects who responded to a self-administered, 40-item evaluation instrument. From 680 possible answers (40 for each one of the 17 participants), the results were: 32 answers (5%) perceived the course as Acceptable; 648 answers perceived it between Good (22%) and Excellent (74%). Taking into account the students’ perception, it is concluded that the course had a high level of quality.